REVIEW AND TAXONOMY OF UAV GUIDANCE - Abdinabiyev, Jasur (Scientific practical conference, 2026)
Unmanned aerial vehicles (UAVs) require advanced guidance systems to perform complex missions in dynamic environments. This paper presents a structured review and taxonomy of UAV guidance approaches, classifying them based on objectives, control strategies and information sources. Classical methods, such as geometric and kinematic guidance, are discussed alongside modern techniques including optimal, robust, adaptive, and intelligent approaches.